Beyond Compliance: The Role of ESG Reporting and Green Accounting in Enhancing Long-Term Value Creation - Sisca Mediyanti; Syarifah Mauli Masyitah; Yusra; Muhammad Ridha Ramli (Universitas Pelita Harapan, 2025)
This conceptual paper explores the strategic role of green accounting in strengthening ESG (Environmental, Social, and Governance) reporting among publicly listed companies in Indonesia. Although the Financial Services Authority (OJK) has made sustainability reporting mandatory, current disclosure practices remain largely compliance-driven and disconnected from internal decision-making processes. Drawing on recent academic literature, the paper argues that ESG reporting alone is insufficient to foster long-term value creation unless it is supported by systematic measurement of environmental impacts through green accounting. While ESG reporting provides an external disclosure platform, green accounting generates decision-relevant information by quantifying environmental costs and translating them into financial terms. The paper reviews existing ESG reporting regulations in Indonesia, describes key elements of green accounting, and clarifies the conceptual linkage between the two. It then proposes a conceptual framework that positions green accounting as an integral component of ESG disclosure, enabling companies to internalize environmental risks and adopt more proactive sustainability strategies. This framework consists of three pillars: environmental measurement and valuation, ESG information integration, and strategic decision-making. The paper concludes that more integrated ESG–green accounting practices have the potential to shift sustainability reporting beyond symbolic compliance and enhance long-term value creation in Indonesian listed companies.